Proceedings of the 2013 International Conference on Software and System Process 2013
DOI: 10.1145/2486046.2486064
|View full text |Cite
|
Sign up to set email alerts
|

Building lean thinking in a telecom software development organization: strengths and challenges

Abstract: The potential shown by Lean in different domains has aroused interest in the software industry. However, it remains unclear how Lean can be effectively applied in a domain such as software development that is fundamentally different from manufacturing. This paper explores how Lean principles are implemented in software development companies and the challenges that arise when applying Lean Software Development. For that, a case study was conducted at Ericsson R&D Finland, which successfully adopted Scrum in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…The literature review supported this approach (Dikert et al 2016) as several companies reported that customization of the agile approach is an evolutionary process, see e.g. (Rodríguez et al 2013;Ryan and Scudiere 2008).…”
Section: Lesson 1: Experimental Transformation Approachmentioning
confidence: 89%
See 2 more Smart Citations
“…The literature review supported this approach (Dikert et al 2016) as several companies reported that customization of the agile approach is an evolutionary process, see e.g. (Rodríguez et al 2013;Ryan and Scudiere 2008).…”
Section: Lesson 1: Experimental Transformation Approachmentioning
confidence: 89%
“…Two of the papers (Abdelnour-Nocera and Sharp 2007; reporting on the same case concentrated on the effects of the agile transformation. A study about Ericsson R&D Finland (Rodríguez et al 2013) 2 focused on how Lean thinking is implemented, however the focus was mostly on the current state instead of the transformation process. A paper from Nokia Siemens Networks (Korhonen 2012) studied whether the visibility, reaction speed, quality, or motivation had changed, comparing the situation before and after the transformation.…”
Section: Large-scale Agile Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Shahid Mujtaba identify waste-related problems in a software product customization process by using value stream maps (VSM) [18] but they did not provide empirical evaluation of value stream maps in the software engineering. Pilar Rodríguez [19] presented some of challenges when applying Lean Software Development as achieving flow, transparency and creating a learning culture but unfortunately did not elaborate on ways to overcome these challenges. Henrik Jonsson [20] provided a framework for lean software development but he did not provide empirical evidences.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, we illustrate our experiences through two case studies conducted in collaboration with Ericsson and Elektrobit in which a similar design science framework was applied ( [8] and [9]). The context of our on-going research is the adoption of Lean Software Development by software intensivecompanies.…”
Section: Introductionmentioning
confidence: 99%